Genetic variants in GCKR, GIPR, ADCY5 and VPS13C and the risk of severe sulfonylurea-induced hypoglycaemia in patients with type 2 diabetes - Holstein, J. D.; Patzer, O.; Körner, A.; Stumvoll, M.; Kovacs, P.; Holstein, A. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Severe hypoglycaemia (SH) induced by sulfonylureas is a life-threatening condition. We hypothesized that recently identified polymorphisms associated with insulin secretion in GCKR, GIPR, ADCY5 and VPS13C genes affect the response to sulfonylureas in patients with type 2 diabetes (T2D) and so, result in reduced risk for SH.We assessed the prevalence of GCKR, GIPR, ADCY5 and VPS13C polymorphisms in a case-control study including 111 patients with SH and 100 patients with T2D but without a history of SH. All patients were treated with the sulfonylurea drugs glimepiride, glibenclamide or gliquidon. SH was defined as a symptomatic event with blood glucose of <50 mg/dl requiring treatment with intravenous glucose.In logistic regression analyses, a low HbA1c and a higher sulfonylurea dose appeared to be the only predictors of SH (P=0.001 and P=0.04, respectively). There was no significant difference in the genotype distribution between the control group and the cases with SH for any of the investigated polymorphisms (OR and 95% confidence intervals – 0.90 (0.59–1.38) for GCKR; 1.11 (0.67–1.85) for GIPR; 0.75 (0.48–1.17) for ADCY5; 1.43 (0.95–2.15) for VPS13C; all P-values >0.05). Also, there was no significant effect of the examined genetic variants on HbA1c levels (all P-values >0.05 adjusted for age, sex, BMI, diabetes duration, sulfonylurea dose).We found no detectable effect (with an OR >2.1) of the variants in GCKR, GIPR, ADCY5 and VPS13C on the response to sulfonylurea treatment, indicating that these variants are not significantly contributing to the risk of SH in patients with T2D.
Keywords: sulfonylurea; severe hypoglycaemia; polymorphisms; type 2 diabetes